PEMAHAMAN KONSEP KUNCI GEOGRAFI UNTUK MENINGKATKAN LITERASI GEOGRAFIS SISWA SMAN 2 BANGKO KABUPATEN ROKAN HILIR, RIAU (Studi Kasus Materi Keanekaragaman Hayati Fase F Kelas XI) (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the application of key geographic concepts (space, place, interconnection, and change) in improving students' geographic literacy on biodiversity material. This study uses a mixed method approach with a sequential explanatory design, which combines quantitative and qualitative data. The subjects of the study were grade XI students of SMAN 2 Bangko Rokan Hilir Regency, Riau. Data collection techniques were carried out through pre-tests and post-tests as well as interviews with geography teachers. The results of the study showed an increase in student literacy as indicated by an increase in the average score from 59.26 in the pre-test to 64.51 in the post-test. The results of the N-Gain analysis showed that the increase was in the moderate category with more prominent developments in higher-order thinking indicators, namely the ability to integrate, evaluate, and use information. In addition, the interview results showed that students became more active and had a high interest in learning after implementing learning based on key geographic concepts, so that the application of key geographic concepts made a positive contribution to improving students' geographic literacy.